The E3 Ubiquitin Ligase SIAH1 Targets MyD88 for Proteasomal Degradation During Dengue Virus Infection - Murphy Schafer, Ashleigh R.; Smith, Jessica L.; Pryke, Kara M.; DeFilippis, Victor R.; Hirsch, Alec J. (Frontiers in Microbiology, 2020)
The dengue viruses present a serious threat to human health globally and can cause severe, even life-threatening illness. DENV is endemic on all continents except Antarctica, and it is estimated that more than 100 million people are infected each year. Herein, we further mine the data from a previously described screen for microRNAs that block flavivirus replication. We use miR-424, a member of the miR15/16 family, as a tool to further dissect the role of host cell proteins during dengue virus infection. We observed that miR-424 targets the E3 ubiquitin ligase SIAH1, expression of which is normally induced during DENV2 infection through the virus's triggering of the unfolded protein response (UPR). Specific siRNA-mediated knockdown of SIAH1 also results in inhibition of DENV replication, demonstrating that this target is at least partly responsible for miR-424's antiviral activity. We further show that SIAH1 binds to and ubiquitinates the innate immune adaptor protein MyD88, and that the antiviral effect of SIAH1 knockdown is reduced in cells in which MyD88 has been deleted by CRISPR/ Cas9 gene editing. Additionally, MyD88 dependent signaling, triggered either by DENV2 infection or the TLR7 ligand imiquimod, is increased in cells in which SIAH1 has been knocked down by miR-424 or a specific siRNA. These observations suggest an additional pathway by which DENV2 harnesses aspects of the UPR to dampen the host innate immune response and promote viral replication.